An analysis of mathematical problem solving ability based on hard work character in mathematics learning using connecting organizing reflecting extending model - Purwati, Lina; Rochmad, Rochmad; Wuryanto, Wuryanto (Unnes Journal of Mathematics Education, 2018)
Mathematical problem-solving ability is one of the goals of mathematics learning. However, the mathematical problem-solving ability of students is still lacking. Therefore, this research was conducted (1) to observe whether students problem-solving ability on CORE-modeled mathematical learning passed the minimum criteria of mastery learning or called as KKM included average mastery and proportion mastery, (2) compare the application of CORE model and Jigsaw model on students problem solving ability, (3) increase the mathematical problems solving ability using CORE model and (4) analyze the mathematical problem solving ability observed from hard work character using CORE model. This research used a mixed method with the concurrent triangulation method. The population was VIII grade student of SMPN 12 Semarang. The results showed that: (1) the mathematical problems solving ability on CORE-modeled mathematical learning passed the minimum criteria of mastery learning included average mastery and proportion mastery, (2) students problem solving ability on CORE mathematics learning model and those on Jigsaw mathematics learning model are equal, (3) there was an increase in the mathematical problems solving ability on mathematics learning after CORE model being applied, (4) student who had worked hard trait in the 1st group on mathematics learning showed the ability to solve mathematical problems was better than those in 2nd and 3rd group on mathematics learning.